2009
DOI: 10.1021/bi802242r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipid Binding Specificities of Dysferlin C2 Domains Reveals Novel Interactions with Phosphoinositides

Abstract: Dysferlin is a type II transmembrane protein implicated in Ca(2+)-dependent sarcolemmal membrane repair. Dysferlin has seven C2 domains, which are lipid and protein binding modules. In this study, we sought to characterize the lipid binding specificity of dysferlin's seven C2 domains. Dysferlin's C2A domain was able to bind to phosphatidylserine (PS), phosphatidylinositol 4-phosphate [PtdIns(4)P], and phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P(2)] in a Ca(2+)-dependent fashion. The remainder of the C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(136 citation statements)
references
References 30 publications
6
128
0
2
Order By: Relevance
“…Interestingly, biophysical studies on the C2A domain have determined that this is the only domain in otoferlin that does not bind calcium (12,53). However, studies on the otoferlin orthologues myoferlin and dysferlin have found that the C2A domains of these proteins do bind calcium, supporting the idea that the calcium binding activity of the C2A domain may have diverged among the ferlins (12,19,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, biophysical studies on the C2A domain have determined that this is the only domain in otoferlin that does not bind calcium (12,53). However, studies on the otoferlin orthologues myoferlin and dysferlin have found that the C2A domains of these proteins do bind calcium, supporting the idea that the calcium binding activity of the C2A domain may have diverged among the ferlins (12,19,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Synaptotagmin 1 possesses two C2 domains, with each showing distinct calcium-regulated binding to different phospholipid membranes (28,29), and different SNARE proteins (30,31). Dysferlin has seven putative C2 domains, of which four show potential calcium sensitivity (32), suggesting even more modular complexity.…”
Section: Discussionmentioning
confidence: 99%
“…1, A and B). However, C2 domains from several other proteins do not possess all five aspartate residues yet, in some cases, are still able to bind calcium (Therrien et al, 2009). Therefore, it is unclear from inspection of the sequence as to which domains of otoferlin, if any, bind calcium.…”
Section: Otoferlin Is a Calcium Sensormentioning
confidence: 99%